Acute effects of the food preservative propionic acid on glucose metabolism in humans - Amir Tirosh; Rajesh Garg; Shreya Bhandari; Gail K Adler; Ezra S Hornik; Gillian Murray; Yogesh Yadav; Mahyar Heydarpour; Rita Basu (BMJ Open Diabetes Research & Care)
Introduction Propionic acid (PA) is a common food preservative generally recognized as safe by the US Food and Drug Administration; however, exogenous PA has effects on glucose metabolism that are not fully understood. Our preclinical studies demonstrated exogenous PA increases glucagon, norepinephrine, and endogenous glucose production (EGP).Research design and methods We performed a randomized, placebo-controlled, crossover study in 28 healthy men and women to determine the effect of PA (1500 mg calcium propionate) on these factors. Subjects had two study visits, each preceded by a 1 week, PA-free diet. During each visit, glucose, insulin, glucagon, norepinephrine, epinephrine, and EGP were assessed for 2 hours after oral administration of PA/placebo under resting conditions (protocol 1) and during either a euglycemic (~85–90 mg/dL) or hypoglycemic (~65–70 mg/dL) hyperinsulinemic clamp (protocol 2).Results PA, as compared with placebo, significantly increased: (1) glucagon and norepinephrine during protocol 1; (2) glucagon, norepinephrine, and epinephrine under euglycemic conditions in protocol 2; and (3) norepinephrine, epinephrine, and EGP under hypoglycemic conditions in protocol 2.Conclusion Oral consumption of PA leads to inappropriate activation of the insulin counterregulatory hormonal network. This inappropriate stimulation highlights PA as a potential metabolic disruptor.